Description of the Apalachicola Redhorse (Catostomidae: Moxostoma) - Akin, Daniel R.; Jenkins, Robert E.; Armbruster, Jonathan W. (Zootaxa, 2025)
The Apalachicola Redhorse is a species that has been long known amongst North American ichthyologists and is herein described as Moxostoma antelunare new species. The Apalachicola Redhorse differs from other gray-tailed Redhorses based on a combination of gill raker count, lateral line scale count, and caudal peduncle depth and the species is supported by two potential osteological autapomorphies: a V-shaped notch between the anteromedial and posteromedial processes of the cleithrum and the anterolateral and posteromedial laminae of the hyomandibula of equal size. The Apalachicola Redhorse occupies much of the Apalachicola River drainage of Georgia, Alabama, and Florida as well as Econfina Creek in the St. Andrew’s Bay drainage of Florida.